Pixel chamber: a solid-state active-target for 3D imaging of charm and beauty. (22nd December 2021) - Mulliri, A.; Arba, M.; Bhattacharya, P.; Casula, E.; Cicalò, C.; De Falco, A.; Mager, M.; Marras, D.; Masoni, A.; Musa, L.; Siddhanta, S.; Tuveri, M.; et al.
Abstract: The aim of the pixel chamber project is to develop the first "solid-state bubble chamber" for high precision measurement of charm and beauty. In this paper we will describe the idea for the first silicon active target conceived as an ultra-high granular stack of hundreds of very thin monolithic active pixel sensors (MAPS), which provides continuous, high-resolution 3D tracking of all of the particles produced in proton-silicon interactions occurring inside the detector volume, including open charm and beauty. We will also discuss the high-precision tracking and vertexing performances, showing that the vertex resolution can be up to one order of magnitude better than state-of-the-art detectors like the LHCb one.